Comparative Study on the Chemical Composition of Syrian Sumac (Rhus coriaria L.) and Chinese Sumac (Rhus typhina L.) Fruits - Kossah, Rima; Nsabimana, Consolate; Zhao, Jianxin; Chen, Haiqin; Tian, Fengwei; Zhang, Hao; Chen, Wei (Pakistan Journal of Nutrition, 2009)
In this article, two different sumac species, namely Syrian sumac (Rhus coriaria L.) and Chinese sumac (Rhus typhina L.) were investigated in order to determine and compare the chemical compositions of their fruits. The proximate analysis revealed a significant difference (p